Akselerasi Kompetensi Backend Developer melalui Penguatan Logika Asynchronous JavaScript for Server-Side Development pada Program Bangkit Academy Batch 1 Tahun 2024 - Marzuki Pilliang; Afifah Khaerani A (Nindikayla Institute, 2025)
The dominance of JavaScript in the modern web development ecosystem requires backend developers to master non-blocking programming paradigms to build scalable systems. However, the complexity of asynchronous logic often poses a cognitive barrier for novice developers in managing intensive I/O operations. This Community Service (PkM) activity aims to accelerate the technical competencies of student participants in the 2024 Bangkit Academy Batch 1 Program by strengthening Asynchronous JavaScript concepts on the server side. The implementation method was conducted online nationwide through expert-led instruction sessions, code reviews, and the implementation of callbacks, promises, and async-await within the Node.js environment. The results of the activity indicate a significant increase in participants' capabilities to design efficient and low-latency server workflows. Project-based evaluations prove that a profound understanding of asynchronous logic successfully enhances code quality and participants' technical readiness to face application development challenges at global industry standards.